Developing Interactive Multimedia for Teaching Personal Pronouns for English Learners of Egypt Islamic Boarding and Course Pare - Fatqu Rofiqoh Dewi; Kurnia Maulidya (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2022)
The research objectives were: (1) to discover the needs of the target and the needs of the teaching and learning of the English learners of Egypt Islamic Boarding and Course, and (2) to develop a media for learning English especially in teaching and learning personal pronoun for English learners of Egypt Islamic Boarding and Course. The researcher used R & D as a method. The participants were 4 female and 8 male students who studied English Egypt Islamic Boarding and Course. Lee and Owens Model (2004: 3- 264) were the guidance in developing this media, but the researcher give some modification to develop this. The need analysis was the first step that the researcher did to find out what the participant needs to enjoy in teaching and learning process. It was giving questionnaire to the students and teacher. The basis for developing a material was the result of the needs analysis. The guideline to develop the beginning draft of personal pronoun materials were the course grid that was taken from the need analysis. After the first draft was arranged, the draft was revised by the experts, and they gave the feedback about the draft. And then, the researcher responded the feedback from the experts by revised the feedback. The needs analysis questionnaire and the experts and the feedback from the experts were the instrumentals of the research. The data analyzing of the needs analysis and the judgement of the experts were through statistical data and description of the result of the instruments. The media was conducted by power point application that was modified with the personal pronoun topics. Each unit consists goals, material, and quiz with twenty tasks focusing on personal pronoun. Then try-out media products that have been revised by English learners of Egypt Islamic Boarding and Course. The average value of the percentage of yes amounted to 95% and the percentage does not amount to 5%. This percentage indicates the category can be used without revision. It can be concluded that media products interactive learning on the material of personal pronoun is so practical and interesting that it can be used easily.